Plural Conceptions of Integration of Science and Religion - Zulkifli, Zulkifli; Nurhayati, Cucu; Ruswandi, Bambang; Suralaga, Fadhilah (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractAlong with the transformation of Islamic higher educations into full-fledged universities, the concept of integration of science and religion is their key characteristic. Indonesian education has witnessed the dynamic and development of paradigm, concept, and metaphor for Islamic university’s science integration. Many studies dealing with the paradigm and concept of science integration and its implementation in curriculum design and learning process have been conducted but tend to focus on the monolithic understanding of each university. By distancing itself from the general trend, this study attempted to analyze the plural conceptions of science integration and factors affecting the plural conceptions at UIN Syarif Hidayatullah Jakarta. To achieve the goal, we employed a mixed method of quantitative and qualitative approach with questionnaires distributed to the sample of 147 lecturers, focus group discussion with 25 participants, and library studies. The study found three types of conceptions have developed and co-existed at UIN Syarif Hidayatullah Jakarta, namely official conception, senior academia’s conception, and general lecturers' conception. Each has its formulation and emphasis, although they share some similarities. The study also revealed the institutional factor as context and individual factors, mainly experience and expertise, resulting in the plural conceptions of science integration. Thus, the concept of science integration at an Islamic university should be considered as a dynamic and plural entity.AbstrakSeiring dengan transformasi perguruan tinggi keagamaan Islam menjadi universitas penuh, konsep integrasi ilmu dan agama menjadi karakteristik utamanya, dan pendidikan Indonesia telah menyaksikan dinamika dan pengembangan paradigma, konsep, dan metafora integrasi ilmu di universitas-universitas Islam tersebut. Banyak penelitian yang berhubungan dengan paradigma dan konsep integrasi ilmu serta implementasinya dalam desain kurikulum dan proses pembelajaran telah dilakukan, tetapi penelitian-penelitian tersebut cenderung berfokus pada pemahaman monolitik dari masing-masing universitas. Berbeda dengan itu semua, penelitian ini berusaha menganalisis beragam konsepsi tentang integrasi ilmu dan agama dan faktor-faktor yang mempengaruhi beragam konsepsi tersebut di UIN Syarif Hidayatullah Jakarta. Kami menggunakan metode campuran kuantitatif dan kualitatif dengan teknik kuesioner yang disebarkan kepada 147 responden, Focus Group Discussion dengan 25 partisipan, dan studi kepustakaan. Studi ini menemukan bahwa tiga jenis konsepsi telah berkembang dan hidup berdampingan di UIN Syarif Hidayatullah Jakarta, yaitu konsepsi resmi, konsepsi akademisi senior, dan konsepsi dosen umum. Masing-masing memiliki rumusan dan penekanan sendiri meskipun mereka memiliki beberapa kesamaan. Studi ini juga mengungkapkan faktor kelembagaan sebagai konteks dan faktor individu terutama pengalaman dan keahlian yang mempengaruhi beragam konsepsi integrasi ilmu. Dengan demikian, konsep integrasi ilmu di universitas Islam harus dipahami sebagai entitas yang dinamis dan beragam. How to Cite: Zulkifli, Nurhayati, C., Ruswandi, B., Suralaga, F. (2020). Plural Conceptions of Integration of Science and Religion. TARBIYA: Journal of Education in Muslim Society, 7(2), 142-157. doi:10.15408/tjems.v7i2.18991.